RUANG PUBLIK YANG MEREPRESENTASIKAN KARAKTER KANAL SEBAGAI UPAYA MENGHIDUPKAN KAWASAN GUNUNG SAHARI - Cynthia Eliza Sony; Maria Veronica Gandha (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Gunung Sahari area in Central Jakarta is known for its large road which acts as a link between many areas in Jakarta. Although many vehicles pass by every day, Gunung Sahari itself is not the destination of choice for many people, even though this area was a memorable place of entertainment for Jakarta residents in the past. Nowadays Gunung Sahari area lack of visitors and the image of the area is starting to dim, making this location only a road that is passed by, not to be visited. As a response, a public space is designed to present a new memory for the area in order to revive Gunung Sahari area. The design of this public space borrows the definition and the characteristic from the word 'canal', which originated from the history of Gunung Sahari area’s development. A canal functions as transportation route, irrigation, flood control, and tourist destination, which obviously became the character of Gunung Sahari area in the past. In this context, the designed public space will act as a transit point as well as a place of recreation for residents who circulate around the area to unwind and fulfill their daily needs through a variety of accommodated programs. The building is designed with an open concept to merge indoors and outdoors so that visitors can enjoy the greenery surrounding the site which also contributes a green space for the area. In addition, there are many communal spaces with flexible arrangements that allow space to grow over time. Keywords: Canal; Public Space; Recreation Abstrak Kawasan Gunung Sahari di Jakarta Pusat dikenal dengan jalan besarnya yang berperan sebagai penghubung banyak wilayah di Jakarta. Meski banyak dilalui kendaraan setiap harinya Gunung Sahari sendiri bukan menjadi pilihan destinasi banyak orang, padahal kawasan ini pernah menjadi tempat hiburan warga Jakarta yang cukup berkesan di masa lampau. Kini kawasan Gunung Sahari sudah sepi pengunjung dan citra kawasan yang mulai redup membuat lokasi ini sebatas menjadi jalan yang dilewati bukan untuk disinggahi. Sebagai respon, dirancang sebuah ruang publik untuk menghadirkan memori baru terhadap kawasan agar dapat menghidupkan kembali kawasan Gunung Sahari. Perancangan ruang publik ini meminjam definisi dan karakteristik dari kata ‘kanal’, yang merupakan awal mula dari sejarah perkembangan kawasan Gunung Sahari. Kanal memiliki fungsi sebagai jalur transportasi, irigasi, pengendali banjir, dan tujuan wisata, yang tentunya menjadi karakter kawasan Gunung Sahari di masa lampau. Dalam konteks tersebut, ruang publik yang dirancang akan berperan sebagai titik transit sekaligus tempat rekreasi bagi warga yang bersirkulasi di sekitar kawasan untuk melepas penat dan memenuhi kebutuhan sehari-hari melalui variasi program yang diwadahi. Rancangan bangunan dibuat dengan konsep terbuka untuk meleburkan ruang dalam dengan luar agar pengunjung dapat menikmati penghijauan disekeliling tapak yang juga menjadi sumbangan ruang hijau bagi kawasan. Selain itu disediakan banyak ruang komunal dengan penataan yang fleksibel memungkinkan ruang untuk tumbuh seiring berjalannya waktu.